2004
DOI: 10.1111/j.1365-2672.2004.02329.x
|View full text |Cite
|
Sign up to set email alerts
|

A putative new endophytic nitrogen-fixing bacterium Pantoea sp. from sugarcane

Abstract: Aims: To isolate and identify endophytic nitrogen-fixing bacteria in sugarcane growing in Cuba without chemical fertilizers. Methods and Results: Two N 2 -fixing isolates, 9C and T2, were obtained from surface-sterilized stems and roots, respectively, of sugarcane variety ML3-18. Both isolates showed acetylene reduction and H 2 production in nitrogenfree media. Nitrogenase activity measured by H2 production was about 15 times higher for isolate 9C than for T2 or for Gluconoacetobacter diazotrophicus (PAL-5 sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(93 citation statements)
references
References 30 publications
3
78
0
9
Order By: Relevance
“…Loiret et al (2004) and Taulé et al (2012) reported the prevalence of isolates from this family, commonly described in association with roots and the rhizosphere, showing potential as phosphate solubilizers and producers of a large amount of indoles.…”
Section: Resultsmentioning
confidence: 99%
“…Loiret et al (2004) and Taulé et al (2012) reported the prevalence of isolates from this family, commonly described in association with roots and the rhizosphere, showing potential as phosphate solubilizers and producers of a large amount of indoles.…”
Section: Resultsmentioning
confidence: 99%
“…Strain AG9 was most similar to Pantoea sp (99%) or Erwinia sp (> 97%). In fact, some species of these genera have been renamed (e.g., Erwinia herbicola has been changed to Pantoea agglomerans) (Loiret et al, 2004) and its actual taxonomic position is not well established.…”
Section: Discussionmentioning
confidence: 99%
“…Genus Pantoe sp. was described in rice and soybean (KuklinskySobral et al, 2004;Verma et al, 2001) and species Pantoe aglomerans in sugarcane (Loiret et al, 2004) different from species found this study (P. stewartii). Genus Burkholderia sp.…”
Section: Discussionmentioning
confidence: 81%
“…Luvizotto et al, 2010). Some species were also found and described, such as: Bacillus polimixa (Rennie et al, 1982), Pantoea agglomerans (Loiret et al, 2004) and Gluconacetobacter diazotrophicus (Perin et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation